2001
DOI: 10.1002/gene.1011
|View full text |Cite
|
Sign up to set email alerts
|

Deer mice: “The Drosophila of North American mammalogy”

Abstract: A major benefit of the nearly completed human and laboratory mouse (Mus musculus) genome projects is the ready application of that information to nontraditional species. Now feasible is the application of detailed genetic approaches to the study of a broad range of species and problems heretofore impracticable (O'Brien et al., 1999). One such group is the deer mouse (Peromyscus maniculatus) and congeneric species (Fig. 1). Peromyscines are arguably the most abundant of the native North American mammals, rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 26 publications
0
49
0
Order By: Relevance
“…27; http:͞͞ compare.bio.indiana.edu), which uses Martins' (28) adaptation of Felsenstein's (26) method of analysis. Our phylogeny for these five species was developed from published information on Peromyscus systematics (29), with all branch lengths set arbitrarily to 1.0. It turned out that the statistical strength of all five of our principal results (the relations between BMR and NPP, DMI and NPP, DMI and BMR, DDMI and NPP, and DDMI and BMR) remained unchanged after factoring out effects of phylogeny, so we shall not discuss the contrast analysis further.…”
Section: Methodsmentioning
confidence: 99%
“…27; http:͞͞ compare.bio.indiana.edu), which uses Martins' (28) adaptation of Felsenstein's (26) method of analysis. Our phylogeny for these five species was developed from published information on Peromyscus systematics (29), with all branch lengths set arbitrarily to 1.0. It turned out that the statistical strength of all five of our principal results (the relations between BMR and NPP, DMI and NPP, DMI and BMR, DDMI and NPP, and DDMI and BMR) remained unchanged after factoring out effects of phylogeny, so we shall not discuss the contrast analysis further.…”
Section: Methodsmentioning
confidence: 99%
“…1 comparisons and links to protein function. In contrast, Peromyscus has been studied extensively in the wild and is a speciose genus with well-documented diversity in reproductive morphology, physiology, ecology, behavior, and mating system (Kleiman 1977;Wolff 1989;Dewey and Dawson 2001). Because Peromyscus exhibit a range of reproductive isolation among populations, subspecies, sister species, species, and species groups (Dice 1933;Liu 1953;Maddock and Dawson 1974), we can gain a more in-depth understanding of patterns of reproductive protein evolution and their potential consequences for speciation (Coyne and Orr 2004).…”
mentioning
confidence: 99%
“…Genetics, stress and glucose regulation RESEARCH ARTICLE (BW) showing geographic ranges of the two species (maps), population origins of the captive stocks (lines), and selected differences (below) (Dawson et al, 1993;Dewey and Dawson, 2001). The BW stock is derived from P.m. bairdii trapped in Washtenaw Co, MI; the PO stock is derived from P. polionotus subgriseus in Ocala National Forest, FL.…”
Section: Dmmbiologistsorg 256mentioning
confidence: 99%
“…Deer mice (Peromyscus) are the most common native North American mammals and inhabit nearly every terrestrial habitat on the continent (Dewey and Dawson, 2001). A study of five Peromyscus species suggested a correlation between metabolic rate and local caloric availability (environmental productivity) (Mueller and Diamond, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation